Gonial angle and its association with mandibular residual ridge resorption in implant-overdenture patients / Pl. Ranganayakidevi S. Palaniappan - Pl. Ranganayakidevi, S. Palaniappan (2019)
Purpose: This study aimed to investigate various methods of gonial angle measurements and to determine the association between gonial angle and residual bone resorption in edentulous patients provided with implants overdenture. Materials and method: 23 patients wearing maxillary complete dentures opposing mandibular implant overdenture prosthesis were recruited. The posterior ridge resorption was measured using the proportional area index method, whereby the dentopantomograph (DPT) of pre- and 4 years post- implant placement of these patients were compared. Mandibular gonial angle measurements were done on 5 out of the 23 patients using four measurement methods: (i) Two different vertical line tracing points on DPT (exterior border points and mid-condylar points), (ii) Manual measurement on 3D printed mandibular model using goniometer, (iii) Lateral cephalometric view of CBCT using Mimics software. The results from each measurement methods were then compared. Results: The results showed a strong association between CBCT measurements and both DPT measurement methods (R2 = 0.927, 0.829), but weak association between CBCT and to the manual measurement on the 3D printed models (R2 = 0.098). However, the associations were not significant (p>0.05). The mean (SD) for the exterior border points method was 128.76⁰ (7.82), while for the mid-condyle points method was 130.89⁰ (7.06) however, the difference was not significant (p = 0.185). The posterior ridge resorption in implant overdenture patients showed no correlation with gonial angle (r < 0.3, p>0.05) as measured on DPT images. v Conclusion: No significant difference between the different gonial angle measurement methods was observed in this study. No correlation between the mandibular gonial angle and posterior mandibular bone resorption was found.